Significance of intratumoral microvessel density quantification based on immunohistochemical detection of PECAM-1 and vWF in colorectal carcinoma from Iraqi patients - Ahmed Mohanad; Mohammed Suhad (Indian Journal of Pathology and Microbiology, 2010)
Context: Counting of newly formed microvessel may prove to be a useful tool in the early detection of metastatic potential and selection of patients for whom antiangiogenesis drugs might be beneficial. Aims: We designed this study to assess the significance of microvessel quantification in colorectal cancer with respect to different clinicopathological variables. Materials and Methods: Forty archived paraffin-embedded colorectal adenocarcinoma samples and their resection margins were enrolled in our study. Thin paraffin-embedded sections (3-5 ΅m thick) of both tumor and resection margins were prepared for each respective biopsy and were used to detect endothelial cell (EC) surface expression of PECAM-1 and vWF by immunohistochemistry technique. Statistical Analysis: For the comparison between tumor and resection margin regarding the investigated parameters, the t-test of significance was conducted. The association between surface expression of PECAM-1 and vWF along with tumor differentiation, depth of invasion and lymph node metastasis was performed by Chi-square (χ2 ) and ANOVA test as well as 95% confidence interval. On the other hand, the association between the investigated parameters and tumor stage as well as tumor size was performed by student t-test. The correlations between the two investigated parameters in respect to various clinicopathological parameters were calculated by correlation coefficient (r). Statistical significance was defined as P < 0.05. All statistical analyses were performed using SPSS statistical package for social and medical science version 15.0. Results: Based on the current outcome, there were significant differences in microvessel density based on PECAM-1 or vWF immunostaining when each tumor sample was compared to its respective resection margin (P < 0.001 and P < 0.001, respectively). In addition, tumors ≥3 mm 3 in size demonstrated a significant increase in their microvessel density compared to their counterparts whether PECAM-1 or vWF immunostaining was applied (P < 0.001 and P < 0.001, respectively). Moreover, when tumor samples were analyzed based on their depth of invasion, for intratumoral microvessel count, exclusively, vWF immunostaining analysis demonstrated significant differences among the three groups: submucosa into muscularis propria (SMP), tumor reaches serosa (SE) and tumors invade other organs (OR), since the latter came up with the highest microvessel count (P < 0.05). When tumor lymph node metastases were questioned, exclusively, vWF immunostaining were significantly differentiated among N0, N1 and N2 groups (P < 0.05). Concerning the possible correlations between the two investigated parameters in respect to various histopathological variables, both PECAM-1 and vWF immunostaining demonstrated significant positive correlations in tumor samples (r = 0.37), whereas in resection margins, these correlations were absent. Although, PECAM-1 and vWF immunostaining revealed significant and positive correlations within tumor differentiation (WD: r = 0.56, MD: r = 0.57 and PD: r = 0.89) as well as with tumor stage (A-B: r = 0.39 and C-D: r = 0.31), still, they seem to correlate significantly and exclusively within SE group (r = 0.74), tumors <3 mm 3 in size (r = 0.66), N0 (r = 0.36) and N1 (r = 0.85) groups. However, PECAM-1 and vWF immunostaining revealed significant but negative correlation exclusively within N2 group (r = -0.38). Conclusion: In conclusion, microvessel count could be useful as a predictor for tumor metastases in patients with colorectal adenocarcinoma. Possible interpretations of the current outcome are explained thoroughly in the text.